Analysis of Corporate Control: Can the Voting Power Index Outshine Shareholding Size? - Norkhairul Hafiz Bajuri; Shanti Chakravarty; Noor Hazarina Hashim (Asian Academy of Management Journal of Accounting and Finance, 2014)
Shareholding size is a poor proxy for corporate control. At best it reflects an investor’s wealth relative to other shareholders and, most importantly, the distribution of rights to a company’s worth and the related exposure to risk. Shareholding size does not actually show an investor’s strength in corporate control. As an alternative, this paper espouses the merits of the voting power concept and promotes two indices associated with it: the Penrose-Banzhaf index and the Shapley-Shubik index. This paper further introduces a new framework that compares the strength of corporate control against the size of corporate shareholding. Illustrating this idea using a group of government-linked companies (GLCs), this study yielded two possible ways in which the government can consolidate its control.